Enhancing Educational Quality: The Impact of Personality, Leader Values, Regulatory Focus, and Servant Leadership on Academic Performance - Rusliana, Iu; Pribadi, Pandu (International Journal of Educational Management and Innovation, 2025)
Background. This study aims to investigate the impact of leader personality, leader values, regulatory focus, and servant leadership on educational quality, specifically at the primary and secondary school levels in Tangerang City. Methods. Using a quantitative approach with descriptive methods, data were collected from 474 school principals through a structured questionnaire. The analysis was conducted using a Structural Equation Modeling (SEM) model based on Partial Least Squares (PLS). Results. The results showed that personality, core values, and regulatory focus significantly influenced servant leadership, which in turn had a positive impact on improving education quality. The findings also reveal that servant leadership plays a mediating role in the relationship between the three variables and education quality. Conclusion. This study emphasizes the importance of developing servant leadership attributes such as empathy, awareness and commitment to human growth in improving education quality. This study makes a new contribution to the educational leadership literature by integrating psychological and behavioral aspects in the context of primary and secondary school management.